Phytochemical composition and pharmacological activities of Teucrium polium L. Collected from eastern Turkey - TAŞKIN, TURGUT (My University, 2022)
© TÜBİTAKTeucrium species that belong to the family Lamiaceae have been traditionally used for their medicinal properties. T. polium is one the most widespread members of the genus for its use in the treatment of several diseases. In this study, the essential oil and phenolic composition of the aerial parts from T. polium were assessed by GC-FID, GC/MS, and LC-MS/MS as well as for its total phenolic content. Several extracts such as n-hexane, chloroform, methanol, and infusion were prepared and their antimicrobial, antioxidant, and also acetylcholinesterase activities were studied. According to GC/MS results, ß -caryophyllene (8.8%), t-cadinol (6.2%), (E)-nerolidol (5%), α -cadinol (5.4%), and a-pinene (4.7%) were identified as main constituents of the essential oil. LC MS/MS analysis of the infusion and the methanol extract showed the presence of 15 phenolic compounds. Moreover, the total phenolic content of each sample was also determined and the infusion had the highest percentage of phenolics. To evaluate the antioxidant properties, the samples were tested by using DPPH\" free radical scavenging, FRAP, and CUPRAC activity methods. The infusion showed the strongest radical scavenging activity, whereas n-hexane and chloroform extracts exhibited considerable reducing power effects. The MIC values for all of the examined microorganisms ranged from 15 to 2000 µg/mL with respect to antimicrobial activities.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; Teucrium; GC-GC; MS; antimicrobial; antioxidant activity; LC-MS; ESSENTIAL OIL COMPOSITION; IN-VITRO EVALUATION; ANTIOXIDANT ACTIVITY; CHEMICAL-COMPOSITION; BIOLOGICAL-ACTIVITIES; ANTIBACTERIAL ACTIVITY; ANTIMICROBIAL ACTIVITY; PHENOLIC-COMPOUNDS; MEDICINAL-PLANTS; EXTRACT; Antimicrobial; Antioxidant activity; GC-GC/MS; LC-MS/MS